Determinant Factor that Influence Muslim Consumers to Choosing Restaurant: The role of Halal, Expectation and Attributes - Anton Bawono; Yudi Saputra (Ekonomi Syariah IAIN Kudus, 2021)
Research related to halal food is dominated by halal manufactured products compared to halal restaurants products. Halal is a matter that concerns every aspect of Muslim life including food, it is important to know the factors that affect the purchase of restaurant product, in this case a halal restaurant. This research tries to find determinants of purchasing restaurant food in Indonesia. The model provide time dimension-based. Data collection was carried out through 438 questionnaires for Indonesian Muslim respondents and only 420 questionnaires could be analyzed. This research found that the halal label is not a direct variable that can influence restaurant food purchases. Men and women have different preferences in buying restaurant food. The results of this study are expected to be able to encourage restaurant manufacturers to adopt halal certification to increase sales. This research focuses on looking for determinants of restaurant food purchases, with time dimension-based modeling.